Jewish masculinities German Jews, gender, and history - Baader, Benjamin Maria; Gillerman, Sharon, 1960-; Lerner, Paul. (Bloomington, IN : Indiana University Press, 2012)
Stereotyped as delicate and feeble intellectuals, Jewish men in German-speaking lands in fact developed a rich and complex spectrum of male norms, models, and behaviors. Jewish Masculinities explores conceptions and experiences of masculinity among Jews in Germany from the 16th through the late 20th century as well as emigrants to North America, Palestine, and Israel. The volume examines the different worlds of students, businessmen, mohels, ritual slaughterers, rabbis, performers, and others, shedding new light on the challenge for Jewish men of balancing German citizenship and cultural affil.
Jewish Masculinities final file01.pdf; Jewish Masculinities final file02; Jewish Masculinities final file03; Jewish Masculinities final file04; Jewish Masculinities final file05; Jewish Masculinities final file06; Jewish Masculinities final file07; Jewish Masculinities final file08; Jewish Masculinities final file09; Jewish Masculinities final file10; Jewish Masculinities final file11; Jewish Masculinities final file12; Jewish Masculinities final file13
Includes bibliographical references and index.
Description based upon print version of record.
Keywords: Jewish men -- Germany -- History -- Congresses; Jews -- Germany -- History -- Congresses; Jews -- Germany -- Identity -- Congresses; Germany -- Ethnic relations; Masculinity -- Germany -- Congresses; Subculture -- Germany -- Congresses; History; Social Science; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Minority Studies; Electronic books